The International and Comparative Criminal Trial Project - FINDLAY, Mark (Institutional Knowledge at Singapore Management University, 2002)
The International Criminal Trial Project (ICTP) has been in operation within the Centre for Legal Research (CLR), Nottingham Law school since January 2000. To date the project has succeeded in establishing a global network of scholars researching international and comparative criminal justice. The ICTP examines and compares trial processes and practice in a variety of local, regional and global contexts. The research incorporates particular evaluations of issues and relationships essential to the operation of trial process in different jurisdictions and stages of development. From the focus on the trial the project is producing knowledge about international and comparative criminal justice. In the current global political climate where international terrorist crimes are a focus for the world community, a sharper understanding of comparative criminal justice is vital. The project is achieving this through its research into the operation of the trial across Europe, and in the context of the international tribunals The policy ramifications of the project's work are significant and are already having some impact on the debate regarding international criminal justice reform. In particular our work on victim participation in sentencing, lay participation in the trial, sentencing in the International Criminal Court, and the influence of regional human rights paradigms on local trial structures is at the forefront of comparative criminal justice research. So far the project has published research papers dealing with the synthesis of trial procedures; theory and modelling for international criminal justice; how to do comparative research in the field; and is embarking on a major comparison of trial practice in England and Italy.